2016
DOI: 10.1128/aem.03603-15
|View full text |Cite
|
Sign up to set email alerts
|

Curing the Megaplasmid pTT27 from Thermus thermophilus HB27 and Maintaining Exogenous Plasmids in the Plasmid-Free Strain

Abstract: Stepwise deletions in the only plasmid in Thermus thermophilus HB27, megaplasmid pTT27, showed that two distantly located loci were important for maintenance of the plasmid. One is a minimum replicon including one gene, repT, coding a replication initiator, and the other encodes subunits of class I ribonucleotide reductase (RNR) for deoxynucleoside triphosphate (dNTP) synthesis. Since the initiator protein, RepT, bound to direct repeats downstream from its own gene, it was speculated that a more-downstream A؉T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…To this end, initially, two homozygous strains (Δ pyrE :: kat and Δ pyrE :: blm ) were created by replacing the pyrE gene with a kanamycin and a bleomycin resistant cassette, respectively (Figure 2A). Numerous examples have shown that homozygous gene deletion mutant could be obtained in T. thermophilus in spite of its polyploid genomic background (Angelov et al 2013; Leis et al 2014; Li et al 2015; Ohtani et al 2015; Wang et al 2016). In the experience, when a non-essential gene was targeted by a vector containing an antibiotic resistant marker sandwiched by two homology arms of that target region, near 90% of the resultant transformants were homozygous deletion mutant of that gene.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, initially, two homozygous strains (Δ pyrE :: kat and Δ pyrE :: blm ) were created by replacing the pyrE gene with a kanamycin and a bleomycin resistant cassette, respectively (Figure 2A). Numerous examples have shown that homozygous gene deletion mutant could be obtained in T. thermophilus in spite of its polyploid genomic background (Angelov et al 2013; Leis et al 2014; Li et al 2015; Ohtani et al 2015; Wang et al 2016). In the experience, when a non-essential gene was targeted by a vector containing an antibiotic resistant marker sandwiched by two homology arms of that target region, near 90% of the resultant transformants were homozygous deletion mutant of that gene.…”
Section: Resultsmentioning
confidence: 99%
“…Curing native plasmids, usually of unknown function, often involves tedious counterselection screenings. [37][38][39] Else, spontaneous plasmid-cured strains can be found serendipitously. 36,40 Given the high frequency of A. baumannii strains bearing multiple native plasmids and the difficulties entailed by mutating and manipulating them, this methodology shows a remarkable potential for their study.…”
Section: Deletion Of Cmla5 and Removal Of P1ab5075mentioning
confidence: 99%
“…The genome of T. thermophilus strain HB27 40 is composed of a 1.9 Mb chromosome and a 0.2 Mb megaplasmid with a GC content of 69% 37 . The bacterium is polyploid, containing an estimated 4-5 copies of the chromosome and megaplasmid each 41,42 . Genes encoding enzymes of a carotenoid biosynthesis pathway are located on the megaplasmid, making the cells yellow-pigmented.…”
Section: Identification Of Caldocas9mentioning
confidence: 99%
“…The crtI gene, which encodes a phytoene desaturase, converts colorless phytoene to lycopene early in the carotenoid biosynthesis pathway, and crtI knock-out mutants therefore appear white 43 . Cells are viable without the megaplasmid, but considerably growth retarded 41 . The purA gene, which encodes adenylosuccinate synthase, is located on the chromosome and is essential in adenine biosynthesis.…”
Section: Identification Of Caldocas9mentioning
confidence: 99%